Peptídeo antimicrobiano PEGuilado como potencial biofármaco para o tratamento de pneumonia causada por Acinetobacter baumannii - Júlio César Moreira de Brito (2020)
Reports of bacterial infections and deaths caused by resistant bacteria have increased globally over time. The World Health Organization (WHO) has been warning about the importance of developing new drugs effective against these superbugs. In this context, antimicrobial peptides are considered an alternative since most of them are involved in innate immunity, acting in different ways, and some also show synergism with commercial antimicrobials. LyeTx I is a linear peptide, with 25 amino acid residues isolated from the spider venom Lycosa erythrognatha. Later, it was also obtained by chemical synthesis and has shown potent antimicrobial activity. LyeTx I-b, the LyeTx I derivative that lacks the Hys16 residue, was active against several multidrug-resistant bacteria, including A. baumannii resistant to carbapenems. However, it is known that, LyeTx I-b has high hemolytic, cytotoxic, and reduced in vivo activities. To overcome these limitations, this work proposes the conjugation of LyeTx I-b with mPEG-MAL and tested its activity and toxicity in vitro and in vivo models. The in vivo model was based on multi-resistant bacterial pneumonia caused by Acinetobacter baumannii. In a review study and meta-analysis, there was a significant rate of resistance of A. baumannii to colistin, one of the most potent and toxic antimicrobials registered and used against this bacterium. This analysis showed that the infection rate of this polymyxin-resistant bacterium in the evaluated period (2010 to 2018) was 13% worldwide, with the value reaching 60% in South America. LyeTx I-bPEG showed decreased activity in vitro for several bacteria; however, this reduction was smaller in A. baumannii. In antibiofilm activity and resistance induction, LyeTx I-bPEG was more active than LyeTx I-b. Additionally, LyeTx I-bPEG reduced by up to 12 times the values of hemolysis and, approximately 10 and 2 times, the in vitro toxicity for VERO and HEK-293 cells, respectively. The decrease in toxicity for LyeTx I-bPEG in vivo, compared to LyeTx I-b, was 4-fold in mice. The values found showed that PEGylation was fundamental for the reduction of toxicity and for in vivo activity in a model of A. baumannii pneumonia, considering that LyeTx I-bPEG, injected in the animals effectively fought the infection. At the same time, LyeTx I-b was not active at 0,5mg.kg-1 e 1mg.kg-1 in this model, possibly due to its degradation/elimination before reaching its targets. These results show that the PEGylation of the LyeTx I-b peptide enabled its use in vivo, maintaining significant activity against pneumonia caused by multidrug-resistant A. baumannii.